Bronchial asthma with normal forced expiratory volume in 1 second (FEV1) compared with low FEV1 - Ohwada, Akihiko; Kitaoka, Hiroko (Journal of thoracic disease, 2024)
Cough variant asthma (CVA) is characterized by cough as a sole symptom and normal pulmonary function. However, it is unclear whether CVA really common among asthmatic patients with normal forced expiratory volume in 1 second (FEV1). The aim of this study was to evaluate the incidence of cough alone symptom among the subjects with normal FEV1 and to evaluate their differences from ordinary asthmatic subjects. We defined normal FEV1 as ≥90% predicted based on the article of Kotti GH. Of the patients with normal FEV1, we chose subjects without wheeze, and the duration of cough was not to ask, since the symptoms often occurred with acute exacerbation and timing of visiting a doctor depended on each patient's perception. Test for airway hyperresponsiveness was not performed in this study. Visual analogue scale (VAS) scores for cough and dyspnea, FEV1, and fractional exhaled nitric oxide (FeNO) responsiveness to inhaled corticosteroid (ICS)/long-acting beta2 agonist (LABA) treatment were compared in patients with normal FEV1 and with low FEV1 <90%. Correlations of changes in symptoms with changes of FEV1, FeNO, peripheral eosinophil count, and serum immunoglobulin E (IgE) at single time point were also examined in each group and in overall patients. The participants were 329 physician-diagnosed treatment-naive patients with asthma who were divided into 187 in normal FEV1 and 142 in low FEV1 groups. Cough without dyspnea was present in 16 patients (8.6%) in the normal FEV1 group, suggesting candidates for CVA in this analysis were quite few. Improvement in symptoms after treatment was similar between both groups. But VAS scores of dyspnea were still higher in the low FEV1 group. The degree of improvement in FEV1 after ICS/LABA treatment was less in the normal FEV1 group than in the low FEV1 group, but was still evident. Peripheral eosinophil count, serum IgE, and FeNO values before treatment were lower in the normal FEV1 group. In overall patients, improvements of symptoms after treatment were significantly correlated with FEV1 changes. Improvement of dyspnea was also significantly related to peripheral eosinophil count and change of FeNO, whereas improvement of cough was not related to these T helper 2 (Th2) response markers. Candidates for CVA among the patients with asthma with predicted FEV1 ≥90% were few. Participants with normal FEV1 respond well to ICS/LABA treatment for improvement of symptom. The change of FEV1 after treatment, and the pre-treatment blood eosinophil count, serum IgE, and FeNO were lower in normal FEV1 cases than in low FEV1 cases. These observations suggest asthmatic patients with normal FEV1, including candidates for CVA having just common mild asthma. In overall participants, symptoms of cough and dyspnea were similar, but were not identical in relation to the Th2 background.